Good Utilization, Low Completion Rates of Early Infant HIV Diagnostic Services at a District Hospital in Rural South Western Uganda - Bazira, Joel; Apio, Kevin; Kyambadde, Mark; Nakawungu, Ruth; Nduhuura, Davis; Ayebarirwe, Memory; Orikiriza, Patrick; Kumbakumba, Elias (Research square, 2022)
Introduction: Early Infant Diagnosis (EID) using DNA PCR has been utilized in the diagnosis of HIV worldwide. This study aimed to determine the utilization of EID using DNA PCR. Methods: A mixed methods study involving 164 caregivers and HCWs providing EID services. Quantitative data was analyzed using SPSS software. Qualitative data was analyzed using inductive thematic content analysis. Data was presented in verbatim form as quotes generated from recoded transcripts. Results: 81% (133/164) of the caretakers reported having utilized EID services. There was low level of awareness of the proper frequency and scheduling of tests in the EID program (11%) and poor completion rates with 46.3% of the respondents having completed all the 3 PCR Tests, 12.8 % having done 2 PCR tests and 23.7% had done 1 PCR test. Good knowledge and attitude of health care providers, availability of test kits and follow up of missed appointments were quoted as drivers for good utilization of EID services while long distance from the health facility, delay at the health facility and inconsistencies in turnaround time were reported as barriers to utilization of the service are. Conclusion: There was good utilization of the EID services and low completion rates.
Keywords: Early Infant Diagnosis; Utilization; PCR; HIV testing in children; HEIs (HIV Exposed Infants